Oral and Dental Changes of Dyskeratosis Congenita: A Case Report with Literature Review. Issue 1 (May 2018) - Serindere, Gozde
Dyskeratosis congenita (DC) is an uncommon disease characterized by nail dystrophy, cutaneous hyperpigmentation, leukoplakia, pancytopenia, and malignant transformation. There can be some oral and dental changes such as oral leukoplakia, increase in tooth decay, hypodontia, thinning of enamel layer, aggressive periodontitis, intraoral brown pigmentation, missing tooth, taurodontism, and blunted roots. Most of cases belong to dermatology or pediatrics department. There are few reports about dentistry. The aim of this report is to lay emphasis on this fatal syndrome among dentists about the multisystem findings and oro-dental changes. Thus, this information may aid dentists in early diagnosis. A case of 21-year-old male diagnosed with DC is reported.